Determinants of Corporate Taxpayer Compliance Through The Mediation Role of Tax Planning - Nurhayati Andikasari; Arik Susbiyani; Ni Nyoman Putu Martini; Toni Herlambang (Jurnal Reviu Akuntansi dan Keuangan, 2025)
Purpose:This study aims to empirically examine the factors that influence tax compliance using sanctions, tax rates, tax knowledge, and the mediating role of tax planning. Methodology/approach: The study used a quantitative approach with data collection using a closed questionnaire to 105 corporate taxpayers, answered by managers or business owners in Bali Province. Hypotheses were tested using structural equation modeling (SEM) with Warp PLS 7.0. Findings: The results showed that tax sanctions, tax rates, and tax knowledge have an indirect effect on tax compliance through tax planning Practical implications: In practice, this research is able to become an important source of information to be considered by the relevant government or policymakers in maximizing tax revenue by considering possible loopholes that can be exploited by corporate taxpayers.  Originality/value: The novelty of this research is the development of a research model using tax planning as a mediating role, which is an important issue today and is still rarely researched.